Vericiguat combined with “new quadruple” therapy enhances cardiac function and life quality in patients with heart failure: a single-center prospective study - Zhao, Di; Zhang, Yanjuan; Yong, Yonghong; Wang, Liansheng; Liu, Jiabao (Frontiers in Cardiovascular Medicine, 2024)
Objective To investigate the therapeutic effect of Vericiguat combined with “new quadruple” drugs on patients with heart failure (HF). Methods From December 1, 2022 to February 1, 2024, 103 patients with heart failure were consecutively enrolled from the cardiology clinic or ward of the First Affiliated Hospital of Nanjing Medical University. Before enrollment, the patients’ left ventricular ejection fraction (LVEF), left ventricular end diastolic diameter (LVEDD), N-terminal pro-B-type natriuretic peptide (NT-proBNP), liver and kidney function electrolytes, and Minnesota Living with Heart Failure Questionnaire (MLHFQ) and other indicators were measured. Patients diagnosed with reduced ejection fraction (HFrEF) and with heart failure with mildly reduced ejection fraction (HFmrEF) were treated with Vericiguat combined with “ARNI, BB, MRA, SGLT2i” therapy. Patients diagnosed with preserved ejection fraction (HFpEF) were treated with Vericiguat combined with “ARNI, BB, SGLT2i” therapy. The above indicators were rechecked after 1 month of treatment. Results For all patients, comparison after treatment: LVEF (38.1 ± 8.5% vs. 43.1 ± 8.5%, P < 0.01), LVEDD (60.5 ± 8.1 vs. 58.2 ± 7.3 mm, P < 0.01), NT-proBNP (4,567.8 ± 5,163.9 vs. 1,895.6 ± 2,702.1 ng/L, P < 0.01), MLHFQ (45.72 ± 11.09 vs. 32.29 ± 9.41, P < 0.01). Further subgroup analysis showed that Vericiguat combined with “ARNI, BB, SGLT2i or MRA” improved the LVEF and reduced NT-proBNP levels in patients with HFrEF, HFmrEF or HFpEF. and improved patients’ quality of life scores. The intergroup comparison showed the therapeutic effect of the combination was equivalent in HF caused by myocardial Infarction (MI), dilated cardiomyopathy (DCM) or Valvular Heart Disease (VHD). Conclusion Vericiguat combined with the “new quadruple” therapy has a significant therapeutic effect on patients with heart failure caused by MI, DCM or VHD.